Restriction endonuclease analysis of Penicillium marneffei - Vanittanakom N. (2014)
Forty-six isolates of Penicillium marneffei were differentiated into two DNA types on the basis of their restriction fragment length polymorphisms. Of the 22 human isolates of P. marneffei, 16 (72.7%) were type I and 6 (27.3%) were type II. Of the 23 bamboo rat isolates, 20 from Rhizomys sumatrensis were type I and 3 from Cannomys badius were type II. The soil isolate was type II. These data represent the first molecular epidemiological study of this important emerging fungal pathogen.